Perencanaan Pengurus Wilayah IPPNU Sumut Dalam Edukasi Dampak Pernikahan Di Usia Dini Bagi Remaja Muslim - Aura Jannah; Soiman Soiman (Universitas Cokroaminoto Yogyakarta, 2025)
This research analyzes the plan of the North Sumatra IPPNU Regional Board in educating Muslim teenagers about the negative impact of marriage at an early age. By using descriptive qualitative techniques such as observation, interviews, and literature studies. Based on the results of the research, IPPNU North Sumatra plans educational activities for teenagers about the negative impact of early marriage, including socialization to schools, strengthening cadres, and partnerships with other organizations. Early marriage has been associated with increased school dropout rates, reproductive health hazards, economic instability, and domestic violence. However, in terms of implementation, IPPNU faces problems such as limited access to schools, the dominance of the program in madrasah, and inadequate funding. Nonetheless, IPPNU is committed to reducing the frequency of early marriage by improving more effective and long-term education techniques.